Simulating Fluid Dynamics of the Alive Tissues with Brownian Motion - Dimitrov, D.; Cvetkov, Z.; Guergov, S. (Elektronika ir Elektrotechnika, 2010)
An effort is made to model movement dynamics of atoms and molecules in a fluid of the human body. Thermodynamical and electromagnetic properties of the particles are of main interest. In the current study those are considered to determine their movement features. Ill. 5, bibl. 3 (in English; abstracts in English, Russian and Lithuanian).